لمحات عن دراسة ألا الاستفتاحية في سورة هود وإلا الاستثنائية في سورة البقرة - Mulyani Maiza; Hanomi Hanomi; Yufni Faisol ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2025)
Abstract God has revealed the Qur'an in a clear Arabic tongue, and its language is classical Arabic. The Arabic language became the most important thing to understand the intention of the Qur'an. In this research discusses the word "not" in Surat Hud or else" in Surat Al-Baqarah.This research aims to find out "not the opening in Surat Hud or else the exceptional in Surat Al-Baqarah" This research uses qualitative research and. The type of research used is the method of literary study research because the material to be searched is the search for works in the interpretation." As for the results of this research, the opening in Surat Hud or else the exceptional in Surat Al-Baqarah." The word "Ala" in Surat Hud: three types and the word "except" in Surat Al-Baqarah: five types.